Orientasi Nilai Budaya Masyarakat Nias dalam Maena pada Upacara Falöwa - Titian Berkat Gea (Universitas Mulawarman, 2021)
This study aims to describe the orientation of Nias cultural values ​​in the lyrics of the maena at the falöwa traditional ceremony in Gunungsitoli. The research was conducted using a qualitative method with an anthropolinguistic approach. The data in this study is a snippet of the lyrics of the maena at the traditional falöwa (wedding) ceremony, either spoken orally or a collection of written lyrics. Primary data sources are the results of interviews with informants and recordings of playing. The secondary data source is the maena lyric text in the book